2015
DOI: 10.1021/ie503729a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MnSO4 on the Removal of SO2 by Manganese-Modified Activated Coke

Abstract: In this study, the effect of manganese sulfate (MnSO 4 ) on desulfurization capacity was investigated through carrying out consecutive desulfurization−regeneration cycles of MnO 2 -blended activated coke (Mn/AC). It was observed that MnSO 4 was produced on the surface of Mn/AC during the desulfurization process, and the amount of MnSO 4 accumulated on Mn/AC first increased significantly and then became relatively stable. In addition, the desulfurization results of MnSO 4 -impregnated Mn/AC indicate that Mn 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…14,23 The results indicated that the natural minerals containing MnO 2 , such as pyrolusite, can be used as the additive to prepare modied activated coke for ue gas desulphurization with low cost and high desulphurization performance. 14,23 The results indicated that the natural minerals containing MnO 2 , such as pyrolusite, can be used as the additive to prepare modied activated coke for ue gas desulphurization with low cost and high desulphurization performance.…”
Section: Introductionmentioning
confidence: 99%
“…14,23 The results indicated that the natural minerals containing MnO 2 , such as pyrolusite, can be used as the additive to prepare modied activated coke for ue gas desulphurization with low cost and high desulphurization performance. 14,23 The results indicated that the natural minerals containing MnO 2 , such as pyrolusite, can be used as the additive to prepare modied activated coke for ue gas desulphurization with low cost and high desulphurization performance.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of SSA, V tot and V mic in the rst few cycles is due to the formation of metal sulphates during the SO 2 removal; the removed SO 2 primarily transformed to form sulphate, and they could not decomposed at the regeneration temperature. 21 With the increasing number of regeneration cycles, there is a higher ratio of removed SO 2 stored in AC as sulphur acid. The sulphuric acid, reacting with carbon, played the role of further activation of ACP and improved its porosity.…”
Section: The Continuous Denitrication and Desulfurization Performancementioning
confidence: 99%
“…19 The linearly reduced desulfurization performance of ACP-Rn was primarily due to its large content of metal sulphate dispersed on the surface, which limited the catalytic oxidation of SO 2 on the surface of catalystsorbent. 21 3.2.3 Surface metal chemistry. The X-ray powder diffraction (XRPD) of ACP and ACP-Rn was applied to clarify the metal chemistry.…”
Section: The Continuous Denitrication and Desulfurization Performancementioning
confidence: 99%
See 2 more Smart Citations